2022
DOI: 10.3389/fpubh.2022.1090677
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and readiness to undertake biodebridement in the group of nurses undertaking prevention and treatment of chronic wounds

Abstract: IntroductionStress as the body's response to adverse stimulus is recognized as one of the key problems in basic and clinical neurological studies. Stress is an indispensable component of modern nursing with its low doses being desirable, however, prolonged stress is detrimental to health increasing the risk of chronic disease i.e., hypertension, cardiovascular diseases, electrolyte disturbances, occupational burnout, depression, anxiety disorders. The implementation of certain techniques and therapeutic method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…These findings build upon the results of earlier studies [16,21,27,28], especially defining the insignificant role of gender in influencing therapist attitudes towards maggot therapy and supporting the association of knowledge and wound care experience with greater comfort about maggots and maggot therapy.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These findings build upon the results of earlier studies [16,21,27,28], especially defining the insignificant role of gender in influencing therapist attitudes towards maggot therapy and supporting the association of knowledge and wound care experience with greater comfort about maggots and maggot therapy.…”
Section: Discussionsupporting
confidence: 81%
“…Some nurses describe their initial experiences with MDT therapy as being stressful, accompanied by sleep disturbances, ruminations, and visions of maggots wriggling in the wound [12,14]. Przybek-Mita et al [16] found that the level of this stress may reduce the readiness to implement this modality in therapeutic protocols. Other studies have also suggested that gender may play a role in the acceptance of maggot therapy [21,27], although these differences did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations